The Effectiveness of Insurance Claim Investigations in Detecting and Uncovering Criminal Fraud in Motor Vehicle Accident Claims (Case Study at PT Tujuh Bintangmas Perkasa) - S. Untung Pambudi; Suardi Suardi (HUMANIORUM, 2025)
The effectiveness of insurance claim investigations in detecting and uncovering criminal acts of Fraud in motor vehicle accident claims, with a case study conducted at PT Tujuh Bintangmas Perkasa. The method used includes a normative and empirical approach, involving direct interviews with company management and investigation teams. The results from these interviews show that claim investigations serve not only as an administrative verification tool but also as a legal instrument to strengthen the company’s position during reporting and law enforcement processes. Based on Article 251 of the Indonesian Commercial Code (KUHD) and Articles 378 and 381 of the Criminal Code (KUHP), investigations play a crucial role in proving the presence of bad faith by the insured party, such as concealing the vehicle’s damage history or forging documents. The investigation team operates under strict Standard Operating Procedures (SOPs) that include scene reconstruction, visual and forensic evidence analysis, and cross-verification of data from the initial policy application. However, several challenges remain, including limited coordination between institutions and insufficient human resources. To improve effectiveness, it is necessary to integrate national data systems, provide regular training for investigators, and optimize technologies such as big data and artificial intelligence (AI). The study concludes that a systematic claim investigation process supported by strong regulations can serve as a primary defense mechanism against Fraud, while also promoting a more transparent and legally compliant insurance industry.